Novel approaches in zero taper, fast drilling of thick metallic parts by ultra-short pulse laser. (July 2019) - Mincuzzi, G.; Faucon, M.; Kling, R.
Highlights: Trepanning head and hybrid process approach enable thick part drilling (up to 2 mm). High power fs lasers are required for high AR holes drilling with negligible HAZ. Step by step analysis leads to time processing reduction: 30 s, AR = 10, zero taper. Abstract: Use of high average power, high repetition rate, ultra-short pulse lasers jointly with trepanning head (enabling both beam rotation and inclination) has been shown to be an effective tool to obtain holes with high machining quality, zero or even negative taper, aspect ratio as high as > 10 and high throughput. Nevertheless, in standard operating conditions (focal length 50 mm – 100 mm, spot size of 20–30 μm, and pulse energy comprised between some tens and hundred μJ), this technological approach shows its limitations when material thickness is higher than nearly 1 mm. Here a novel approach is proposed consisting of a top-down, hybrid (sequence of trepanning, drilling and trepanning) drilling process. By systematic variation of process parameters (beam inclination angle, focus re- positioning, etc.) this approach has been optimized to drill zero tapering holes in stainless steel 316 L having a thickness varying from 0.9 mm to 2 mm. An analysis of the impact induced by each process step on the hole evolution (both geometry and ablated volume) has been carried out and in particular the role it plays on the hole shape evolution the dust generated by the material ablation before to be evacuated, has been highlighted. Importantly, a zero-tapering hole with aspect ratio of 10 was obtained in a 2 mm thick sample with a processing time of 32 s. Finally, an analysis of the thermal effects on the internal part of the holes was carried out by SEM micrograph and here reported.